Exploring Junior High School EFL Teachers’ Digital Literacy in Digital Resource Adaptation - Hasnada, Taqina; Wirza, Yanty (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2026)
Digital literacy has emerged as a crucial skill for teachers to acquire in order to adapt to the enormous digital learning resources available online. This study aims to explore English teachers’ digital literacy knowledge and practices, particularly their adaptation of digital learning resources for classroom use. This study employed a qualitative content analysis design guided by the European Framework for the Digital Competence of Educators(DigCompEdu). The study focuses on three areas: digital resources, teaching and learning, and empowering learners, to map teachers’ competence against their classroom practices. Data were collected from 12 digital learning resources created by three junior high school English teachers, supported by DigCompEdu-derived questionnaires and semi-structured interviews. Although the sample is small, the study adopts an in-depth case-oriented approach to generate rich, contextualized insights into the relationship between perceived and enacted digital competence. The findings reveal a significant disparity between teachers’ self-assessed competence levels (B1–C1) and the pedagogical depth of their resource adaptation. While teachers frequently use multimodal resources and demonstrate functional digital skills, critical evaluation of sources, systematic citation practices, learner-centered adaptation, and integration of problem-solving remain limited. This gap highlights a conceptual distinction between operational digital proficiency and profound digital literacy in pedagogical contexts. The novelty of this study lies in its empirical evidence of competence-practice misalignment, based on a triangulated analysis of self-assessment data and real instructional artifacts within the DigCompEdu framework. The findings contribute to global discussions on teachers' digital literacy by emphasizing the need to move beyond skill acquisition toward reflective, evaluative, and pedagogically grounded digital integration in language education